Changes in self-efficacy and oral health habits among adolescents - Leino, Katariina (My University, 2020)
Objectives: The aim of this study was to examine whether there were associations between the simultaneous change in adolescents’ (aged 11-15 years) self-efficacy in relation to the change in tooth brushing frequency and xylitol use in a longitudinal setting. Methods: This is a secondary analysis of a questionnaire data collected longitudinally 2001-2005 from adolescents of Pori, Finland aged 11-15 (n=1308). The associations between adolescents’ self-efficacy, tooth brushing frequency and xylitol use were measured using SPSS Statistics 25. The changes were reported by gender, parents’ education level and age group in a longitudinal setting. The variables were measured using multiple choice questions in three time points. A literature review was conducted using PubMed- and Embase -databases. Self-efficacy, beliefs, oral health habits (tooth brushing and xylitol use) and parents’ education level were analysed statistically using Chi Square test and Mann Whitney U -tests to measure variables in different time points. For longitudinal evaluations Cochran’s Q test and Friedman’s test were used. Results: Girls had higher self-efficacy than boys in all time points (p<0.001). The difference in self-efficacy between genders statistically significantly improves in every time point. In 2001 p<0.05, in 2003 p<0.05 and in 2005 p<0.001. Self-efficacy improved with age in all study groups. The biggest positive change in self-efficacy happened with adolescents aged 11-13 years when they decreased their tooth brushing frequency or xylitol use. Conclusions: There was a slight association with the positive change in self-efficacy and decreasing of tooth brushing or xylitol use habit among adolescents.
Keywords: adolescent, self-efficacy, oral health, xylitol, tooth brushing